Russian Liberalism in Crisis? Khodorkovsky Revisited - White, David (Studies of Transition States and Societies, 2013)
The electoral decline of liberal parties has been a key feature of post-Soviet politics in Russia. Using Mikhail Khodorkovsky’s critique of Russian liberalism as a starting point for analysis, it is argued that a lack of cohesion and unity has undermined support for liberal-democratic forces. Ultimately, however, exogenous factors over which the liberal parties have had no control (the marginalisation of opposition, the restriction of media access and the huge imbalance of resources available to political parties in Russia) have played the major determining role in the liberals’ decline. It is argued that Russia’s two main liberal parties during the Putin years were targeted by the regime because they were opposition parties. In Russia’s electoral authoritarian system, political opposition has been systematically excluded and fragmented, the aim being not just to restrict but to close off any potential opportunities.